Isolation of Enterobacter spp. and Klebsiella pneumoniae from ready-to-eat commercially sold frozen nuggets sold in Dhaka - Banik, Aditya; Mujtabah, Subah Basharat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.